Clinical, hormonal and molecular-genetic characteristics of monogenic diabetes mellitus associated with the mutations in the INS gene - Yu. V. Tikhonovich; E. E. Petryaykina; A. V. Timofeev; N. A. Zubkova; A. A. Kolodkina; E. L. Sorkina; E. V. Vasiliev; V. M. Petrov; E. A. Andrianova; L. I. Zilberman; G. N. Svetlova; A. L. Кalinin; et al. (Сахарный диабет)
Background: Currently more than 50 mutations of the INS gene are known to affect the various stages of insulin biosynthesis in the beta cells of the pancreas. However only individual cases of diabetes mellitus (DM) associated with heterozygous mutations in the coding region of the INS gene were reported in Russian Federation. We report a group of patients with a clinical manifestation of DM caused by mutations in both coding and non-coding regions of the INS gene. The patients with a mutation in the intron of the INS gene are reported for the first time in Russian FederationMaterials and methods: 60 patients with an isolated course of neonatal DM (NDM), 52 patients with a manifestation of DM at the age of 7–12 months and the absence of the main autoimmune markers of type 1 DM, 650 patients with the MODY phenotype were included in the study. NGS technology was used for molecular genetic research. Author’s panel of primers (Custom DNA Panel) was used for multiplex PCR and sequencing using Ion Ampliseq™ technology. The author’s panel “Diabetes Mellitus” included 28 genes (13 candidate genes of MODY and other genes associated with DM).Results: 13 heterozygous mutations were identified in 16 probands and 9 relatives. The majority of mutations were detected in patients with PNDM (18.75%) and in patients with an onset of DM at the age of 7–12 months (9.6%). Mutations in the INS gene were detected in 2 patients (0.3%) in the group with the MODY phenotype. Mutations in the INS gene were not detected in patients with transient NDM (TNDM). Analysis of clinical data in patients with PND and onset of diabetes at the age of 7–12 months did not show significant differences in the course of the disease. The clinical characteristics of the cases of MODY10 and diabetes caused by a mutation in the intron of the INS gene are reported in details.Conclusion: The role of INS gene mutations in NDM, MODY, and DM with an onset at the age of 7–12 months was analyzed in a large group of patients. The clinical characteristics of DM due to a mutation in the intron of the INS gene are reported for the first time in the Russian Federation.